2010
DOI: 10.1186/cc9067
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital percentage BNP reduction is highly predictive for adverse events in patients admitted for acute heart failure: the Italian RED Study

Abstract: IntroductionOur aim was to evaluate the role of B-type natriuretic peptide (BNP) percentage variations at 24 hours and at discharge compared to its value at admission in order to demonstrate its predictive value for outcomes in patients with acute decompensated heart failure (ADHF).MethodsThis was a multicenter Italian (8 centers) observational study (Italian Research Emergency Department: RED). 287 patients with ADHF were studied through physical exams, lab tests, chest X Ray, electrocardiograms (ECGs) and BN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 37 publications
(37 reference statements)
4
39
1
2
Order By: Relevance
“…Data from our group showed that a reduction in BNP > 46% compared to the admission levels, coupled with an absolute BNP value < 300 pg/mL was a very powerful NPV for future cardiovascular outcomes in patients hospitalized with acute decompensated heart failure ( Figure 3) [31]. Furthermore, analysis of a large Medicare database has shown that discharge BNP measurements are the most important characteristic for predicting 1-year mortality (HR 1.34, 95% CI 1.28-1.40) and 1-year death or rehospitalization (HR 1.15, 95% CI 1.12-1.18) among older patients hospitalized with heart failure [32].…”
Section: Bnp Point-of-care Testingmentioning
confidence: 99%
“…Data from our group showed that a reduction in BNP > 46% compared to the admission levels, coupled with an absolute BNP value < 300 pg/mL was a very powerful NPV for future cardiovascular outcomes in patients hospitalized with acute decompensated heart failure ( Figure 3) [31]. Furthermore, analysis of a large Medicare database has shown that discharge BNP measurements are the most important characteristic for predicting 1-year mortality (HR 1.34, 95% CI 1.28-1.40) and 1-year death or rehospitalization (HR 1.15, 95% CI 1.12-1.18) among older patients hospitalized with heart failure [32].…”
Section: Bnp Point-of-care Testingmentioning
confidence: 99%
“…It is interesting to note that, despite the association of higher discharge BNP with worse prognosis even in extremes of natriuretic peptide activation at discharge; BNP changes during hospitalisation did not, as expected (Di Somma et al 2010), predict outcome; probably, these discharge BNP extremes -low and high -are already a mirror of response and non-response, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Az Italian Research Emergency Department (RED) vizsgálat 287 betegében az elbocsátáskori 300 pg/mL feletti vagy <46%-os csökkenést mutató BNP-szint 9,614-es rizikóhányadossal (95% CI: 4,51-20,47) volt prediktív a 180 napos adverz eseményekre (cardiovascularis mortalitás vagy szívelégtelenség miatti hospitalizá-ció) [35]. Az elbocsátás előtti natriureticuspeptid-szint a natriureticuspeptid-szint változásával együtt nemrég egy halálozást és rehospitalizációt előre jelző rizikó-score része lett [36].…”
Section: A Kórházi Felvételi éS Elbocsátás Előtti Natriureticuspeptidunclassified